Implementation of Islamic Religious Value on Governance of Law and Environmental Issue - Mochamad Arief Soleh; Tubagus Chaeru Nugraha; Otong Nurhilal; Asep Agus Handaka Suryana (Islamic Research, 2020)
Social environment is changing rapidly coincide with rapid change of human thinking in solving any problems. The thinking is underlying human activity in their life, so that it needs a guidance of thinking in facing every change in the life. Padjadjaran University (Unpad) as part of educational state has a guidance to support national development which is presented in principal scientific pattern (PSP) consisted of strengthen law and environmental issue. The rise opinions to restore Islamic religious values in the social order such as growing of Islamic banking system have proven its superiority at any challenges of finance problem. Therefore this paper tries to illustrate the superiority of Islamic values that are integrally introduced into PSP of Unpad's vision and mission. One of Islamic religious value has been listed in maqasid sharia is to maintaining human mind (Hifz Al Aql) in thinking and behavior and also to maintaining harmonious environment for good living. Hopefully, all of activities in the academic community of Unpad could be able to rely on Islamic PSP as a guidance in every academic activities, moreover to bring Islam blessings and prosperity for all (rahmatan lilalamiin) at the Unpad.